EVALUATION OF ACCURACY OF WORK OF COMPLEX TECHNICAL SYSTEMS IN FUNCTIONAL EXCESS - Борисюк, Г. Ю.; Тамаргазін, О. А. (Proceedings of National Aviation University (archive), 2021)
Integral characteristics are considered, which allow to assess the accuracy of complex technical systems for all their possible operational states, taking into account the occurrence of failures and (or) the impossibility of using some of the system elements to solve the functional problem.